Internationalization of Higher Education Cooperatives: Economic, Legal, Health, and Technology Synergy through PKM in Malaysia - Handayani, Tuti; Nino Sri Purnama Yanti; Gusmawet; Nurhayati; Oktavianis; Resty Noflidaputri (KPN Kopertis X, 2025)
International community service (PKM) is a tangible manifestation of the involvement of universities in bridging science with practice in the field across countries. This activity was carried out through a mock study and collaboration between Indonesian Higher Education Cooperatives and cooperative institutions in Malaysia, involving economic, legal, health, and technological aspects.